Relationship between Gingival Inflammation and Pregnancy - Min Wu; Shao-Wu Chen; Shao-Yun Jiang (Hindawi Limited, 2015)
An increase in the prevalence and severity of gingival inflammation during pregnancy has been reported since the 1960s. Though the etiology is not fully known, it is believed that increasing plasma sex steroid hormone levels during pregnancy have a dramatic effect on the periodontium. Current works of research have shown that estrogen and progesterone increasing during pregnancy are supposed to be responsible for gingivitis progression. This review is focused not only on epidemiological studies, but also on the effects of progesterone and estrogen on the change of subgingival microbiota and immunologic physiological mediators in periodontal tissue (gingiva and periodontal ligament), which provides current information about the effects of pregnancy on gingival inflammation.